Pyrrole modified biomass derived hierarchical porous carbon as high performance symmetrical supercapacitor electrodes. (10th August 2016) - Wang, Keliang; Xu, Ming; Gu, Zhengrong; Ahrenkiel, Phil; Lee, Joun; Gibbons, William; Croat, Jason; Fan, Qihua
Abstract: Nitrogen-doped hierarchical porous carbon has been prepared via a direct carbonization of pyrrole modified biomass for using as electrochemical double layers capacitance electrodes materials. The hierarchical porous carbon features high specific area (2959 m 2  g −1 ) and porosity, which originated from the etching, gasification and intercalation effect during heat treatment. Based on this unique porous structure, specific capacitance of 270 F g −1 at low current density of 0.1 A g −1 and 232 F g −1 at high current density of 10 A g −1 was obtained in 6 mol L -1 KOH electrolyte. Excellent cycles durability was obtained after initial charge/discharge, the high specific capacitance remained nearly unchanged for total 4000 cycles tested over a broad current density ranging from 0.1 to 10 A g -1 . This study indicates that hierarchical porous carbon derived from pyrrole modified biomass is a promising electrode material for symmetric supercapacitors. Graphical abstract: Highlights: Pyrrole modified fungus was used to prepare supercapacitor electrodes. Efficient and simple KOH activation method was used. Hierarchical structure, high SSA (2959 m 2  g −1 ) and conductivity were exhibited. Excellent specific capacitance of up to 270 F g −1 was obtained. Discharging at large current density (10 A g −1 ) was achieved.